Toxoplasma gondii: CD8 T Cells Cry for CD4 Help - Khan, Imtiaz A.; Hwang, SuJin; Moretto, Magali (Frontiers in Cellular and Infection Microbiology, 2019)
Toxoplasma gondii, an apicomplexan parasite, is a pathogenic protozoan that can infect the central nervous system. In pregnant women, infection can result in congenital problems of the fetus, while in immunocompromised individual it can lead to severe neurological consequences. Although CD8 T cells play an important effector role in controlling the chronic infection, their maintenance is dependent on the critical help provided by CD4 T cells. In a recent study, we demonstrated that reactivation of the infection in chronically infected host is a consequence of CD8 T dysfunction caused by CD4 T cell exhaustion. Furthermore, treatment of chronically infected host with antigen-specific non-exhausted CD4 T cells can restore CD8 T cell functionality and prevent reactivation of the latent infection. The exhaustion status of CD4 T cells is mediated by the increased expression of the transcription factor BLIMP-1, and deletion of this molecule led to the restoration of CD4 T cell function, reversal of CD8 exhaustion and prevention of reactivation of the latent infection. In a recent study from our laboratory, we also observed an increased expression of miR146a levels by CD4 T cells from the chronically infected animals. Recent reports have demonstrated that microRNAs (especially miR146a) has a strong impact on the immune system of T. gondii infected host. Whether these molecules have any role in the BLIMP-1 upregulation and dysfunctionality of these cells needs to be investigated.